Abstracts Analysis on Student’s Final Project Using CARS Theory - Junanto, Heru; Zahrohtul, Galih; Triyawan, Daffa; Suminar, Ratna Prasasti; Wahidah, Farah Sukmawati (CV. Rustam, 2024)
This research aims to describe the moves and steps of the CARS model contained in the final project of Genre Analysis (GA) of English language education for students in Indonesia. This study aims to describe the moves and steps of the Creating a Research Space (CARS) model that is presented in the English-language students' Genre Analysis (GA) theses of several universities in Indonesia. The model used in this study is the CARS model of Swales which consists of three moves. The research method is qualitative. The data in this study are five abstract scripts of students of the English Language Education study program available in Indonesia. Two abstract scripts were obtained from the document repository of the University of Education Indonesia and three abstracts from the documents of the Islamic University of Indonesia for 2023. The data collection technique used is the library, which is the primary data source for the written source. The data analysis techniques used qualitative descriptive techniques. These results show that the Creating a Research Space (CARS) model developed by Swales can be effectively applied to the analysis of abstract genres in English language student scripts. All moves and steps in the CARS model, ie M-1 (creating analysis fields), M-2 (solving problems in analysis), and M-3 (absorbing problems), can be clearly identified in the abstract scripts studied. From this point of view, the researchers emphasize that applying the CARS model not only helps in abstract structural analysis but also provides a deeper insight into how to compose an informative, coherent, and consistent with academic standards.